Analysis of Internalization Project To Strengthen The Profile Of Pancasila Students Based on Local Culture Of Toraja - Kaban Sendana, Aris; Nani Sallata, Yizrel; Teko Patanduk, Sushy (Ethical Lingua: Journal of Language Teaching and Literature, 2025)
This study explores the internalization of the "Project to Strengthen the Profile of Pancasila Students" through the lens of Toraja's local culture. Pancasila, as Indonesia’s foundational philosophical principle, emphasizes values such as mutual respect, social justice, and unity in diversity. By integrating Toraja's rich cultural heritage including its traditions, arts, and social norms this project aims to enhance students' understanding and embodiment of Pancasila values. The research employs a qualitative approach, utilizing interviews, participant observations, and focus group discussions with educators, students, and local community leaders. It highlights the effectiveness of culturally contextualized education in fostering critical thinking, civic responsibility, and a sense of belonging among students. By examining local customs, such as the Toraja's unique funeral rites and communal practices, the project illustrates how these cultural elements can be harnessed to reinforce Pancasila principles in a meaningful way. Findings indicate that incorporating local culture not only enriches students' learning experiences but also cultivates a deeper appreciation for their national identity. The study concludes that the successful internalization of Pancasila values requires a collaborative effort between educational institutions and local communities, promoting a holistic educational framework that respects and celebrates cultural diversity. This approach not only prepares students to become responsible citizens but also strengthens the social fabric of Indonesia by bridging cultural heritage with national ideals. Ultimately, the project serves as a model for similar initiatives in other regions, emphasizing the importance of local culture in national education reforms aimed at nurturing a generation grounded in both local and national values.